The Effect Of Gender And Locus Of Control On The Ethical Perception Of Accounting Students With Love Of Money As Intervening Variables : Pengaruh Gender Dan Locus Of Control Terhadap Persepsi Etis Mahasiswa Akuntansi Dengan Love Of Money Sebagai Variabel Intervening - Febyola, Caesar; Hermawan, Sigit (Indonesian Journal of Innovation Studies, 2021)
This study aims to analyze the influence of gender and locus of control variables on the ethical perceptions of accounting students with love of money as an intervening variable and to find out whether the variable love of money can be an intervening variable on gender and locus of control variables. The analysis used in this study is Partical Least Square (PLS). The hypotheses in this study are: Gender influence on Love Of Money, Locus Of Control influence on LoveOf Money level, Gender influence on Ethical Perception, Locus Of Control influence on ethical perception, Love Of Money has significant influence on Ethical perception, Love Of Money can be an intervening variable on the influence of gender on the ethical perceptions of accounting students, love of money can be an intervening variable on the influence of locus of control on the ethical perceptions of accounting students. The results of this study can be concluded from the results of the tests that have been conducted, namely Gender can affect Love Of Money with a negative influence, meaning that male gender has a negative effect on Love Of Money, while Female Gender has a positive influence on Love Of Money, Locus Of. Control has a positive effect on Love Of Money, Gender has a negative effect on students' ethical perceptions, Locus of Control has an influence on students' ethical perceptions, LoveOf Money has an influence on students' ethical perceptions, Love Of Money as an intervening variable of the Locus Of Control variable has a significant effect Regarding ethical perceptions, Love Of Money as an intervening variable of the Gender variable has no significant effect on ethical perceptions.